Consumer Preferences in Developing Derivative Product of Gluten Free Bread Cookly - Balweel, Thania Usamah; Ratnawati, Anny; Nuraisyah, Ani (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Cookly is a bread manufacturer that uses cassava as the main ingredient to produce gluten-free products. Cookly requires innovative development of derived products that cater to consumer needs. Purpose: This study aims to identify consumer characteristics, analyze consumer preferences, and formulate an innovation plan for Cookly gluten-free derived bread products. Design/methodology/approach: The sample for this study consisted of 100 participants selected through purposive and snowball sampling. Data analysis utilized descriptive analysis and conjoint analysis. Findings/Result: The study found that Cookly consumers were evenly distributed in terms of gender, aged between 18-25, mostly unmarried, residing in Bogor, with a high school education, and working as students or employees, with a monthly expenditure ranging from IDR500,000-IDR3,000,000. Conclusion: The most preferred attribute combination by respondents was a dominant savory taste with relatively low sugar content, a soft texture, bread with color, packaged in environmentally friendly boxes, and priced between IDR10,000-IDR25,000Originality/value (State of the art): Cookly developed a convenient gluten-free bread product, the Gluten-Free Toasted Cassava Bread, with savory flavors offered as signature menu items and a